The Value of Uganda's Forests: A livelihoods and ecosystems approach - Bush, Glenn; Nampindo, Simon; Aguti, Caroline; Plumptre, Andrew (Wildlife Conservation Society., 2004)
Forests provide a wealth of indirect environmental benefits as well as direct use benefits for many of the people surrounding them. The loss of forested areas upsets soil-water relations, creates erosion, and lowers water quality that, in turn has an associated effect on human health. In addition people may gather medicinal plants, fuel wood or derive food from the forests to support their livelihoods and the loss of these habitats leads to a lower quality of life. The importance of these ecosystems in the conservation of biodiversity also has an international dimension; many species are of global value and their habitats of importance in the provision of global public goods such as carbon sequestration.